Investigating the Role of Mobile Devices in a Blended Pre-Service Teacher Education Program - Vaughan, Norman; Lawrence, Kimberley (Canadian Journal of Higher Education, 2013)
The purpose of this research study was to investigate if and how mobile devices could be used to support the required program outcomes in a blended pre-service teacher education degree. All students enrolled in an educational technology course during the fall 2011 semester were provided with ViewSonic tablets. Through faculty interviews, student online surveys, and a post-course focus group, the study participants indicated that mobile devices could be useful for supporting future professional responsibilities (e.g., career-long learning, collaboration) and facilitating student learning but less effective for planning, assessment, and managing the classroom environment.